Lo epistemológico para hablar de administración. (2021)
The management is a social science and so it has to be at the service of the society and not at the service of the dominant capitalism. The social consequences of the present economic model are not satisfactory and the business administration has been an important part of this failure because it has not wondered about its own acts. The complex thought invites to see the business administration in its relations with other sciences , with the society and not only with the capital.